High-sensitivity sequencing reveals multi-organ somatic mosaicism causing DICER1 syndrome. Issue 1 (16th October 2015) - de Kock, Leanne; Wang, Yu Chang; Revil, Timothée; Badescu, Dunarel; Rivera, Barbara; Sabbaghian, Nelly; Wu, Mona; Weber, Evan; Sandoval, Claudio; Hopman, Saskia M J; Merks, Johannes H M; van Hagen, Johanna M; et al.
Abstract : Background: Somatic mosaicism is being increasingly recognised as an important cause of non-Mendelian presentations of hereditary syndromes. A previous whole-exome sequencing study using DNA derived from peripheral blood identified mosaic mutations in DICER1 in two children with overgrowth and developmental delay as well as more typical phenotypes of germline DICER1 mutation. However, very-low-frequency mosaicism is difficult to detect, and thus, causal mutations can go unnoticed. Highly sensitive, cost-effective approaches are needed to molecularly diagnose these persons. We studied four children with multiple primary tumours known to be associated with the DICER1 syndrome, but in whom germline DICER1 mutations were not detected by conventional mutation detection techniques. Methods and results: We observed the same missense mutation within the DICER1 RNase IIIb domain in multiple tumours from different sites in each patient, raising suspicion of somatic mosaicism. We implemented three different targeted-capture technologies, including the novel HaloPlex HS (Agilent Technologies), followed by deep sequencing, and confirmed that the identified mutations are mosaic in origin in three patients, detectable in 0.24–31% of sequencing reads in constitutional DNA. The mosaic origin of patient 4's mutation remains to be unequivocally established. We also discovered likely pathogenic second somatic mutations or loss of heterozygosity (LOH) in tumours from all four patients. Conclusions: Mosaic DICER1 mutations are an important cause of the DICER1 syndrome in patients with severe phenotypes and often appear to be accompanied by second somatic truncating mutations or LOH in the associated tumours. Furthermore, the molecular barcode-containing HaloPlex HS provides the sensitivity required for detection of such low-level mosaic mutations and could have general applicability.